The institutional framework of Russian serfdom - Dennison, T. K. (Tracy K.), 1970-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"Russian rural history has long been based on a "peasant myth" which originated with nineteenth-century Romantics and is still accepted by many historians today. In this book, Tracy Dennison shows how Russian society looked from below, and finds nothing like the collective, redistributive, and market-averse behaviour often attributed to Russian peasants. On the contrary, the Russian rural population was as integrated into regional and even national markets as many of its west European counterparts. Serfdom was a loose garment that enabled different landlords to shape economic institutions, especially property rights, in widely diverse ways. Highly coercive and backward regimes on some landlords' estates existed side-by-side with surprisingly liberal approximations to a rule of law. This book paints a vivid and colourful picture of the everyday reality of rural Russia before the 1861 abolition of serfdom"--Provided by publisher.
Why is Russia different? : culture, geography, institutions -- Voshchazhnikovo : a microcosm of nineteenth-century Russia -- Household structure and family economy -- The rural commune -- Land and property markets -- Labour markets -- Credit and savings -- Retail markets and consumption -- The institutional framework of Russian serfdom.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Serfdom -- Russia -- History; Peasants -- Russia -- Economic conditions; Peasants -- Russia -- Social conditions; Land tenure -- Russia -- History; Right of property -- Russia -- History; Agriculture -- Economic aspects -- Russia -- History; Agriculture -- Social aspects -- Russia -- History; Russia -- Rural conditions; Russia -- Economic conditions -- To 1861.; Russia -- Commerce -- History; Electronic books